WEB-BASED E-DOCUMENT INFORMATION SYSTEM - Zulkifly Fadly Pratama; Novita Br. Ginting; Safaruddin H. Al Ikhsan (Jurnal Mantik, 2021)
AbstractAn authentic deed essentially contains the formal correctness of the information in accordance with what the client has told the notary public, therefore legal protection is required for the notary in carrying out his position. The success of a notary can not only be measured by the number of deeds he makes, but also from the deeds' expertise to the storage of client information documents. The large number of deed makers without neat and orderly document storage will cause problems and difficulties in the future. Notary and PPAT Afri Siswatuti, SH., MKn. Still using the manual method of storing documents, so when these documents are needed they must first be searched manually on the document index, so it takes time in the search process. To solve this problem, it is necessary to build an information system to help manage documents that have been made that can be stored and organized neatly by creating a web-based e-document information system which contains the process of making notary letters to storing documents for clients. The output of this research is a web-based deed management information system design. So that documents can be managed properly in a short time, data retrieval becomes more efficient.